THE EFFECT OF QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY ON STUDENTS' ACHIEVEMENT IN READING COMPREHENSION - Angelia Yemima Butar butar; Sinta Hotma Yanti Haloho; Debora Sipahutar; Rini Destina Marbun; Nurmahyuni Asrul (Esteem Journal of English Education Study Programme, 2022)
The focus of this research is to demonstrate the influence of question-and-answer learning on students' reading interest in narrative texts. Is there an effect of question answer relationship strategy on students' reading skills in reading narrative texts? Class Vlll SMP Methodist 9 Medan is the problem in this research. This form of research is a quasi-experimental study that includes an experimental and a control group, as well as pre- and post-tests. The post-test results showed that 22 pupils (88 percent) received very high scores and 3 students (12 percent) received high scores. The experimental group's mean score was likewise raised. Prior to using the QAR technique, the mean was 67.04. The mean after learning using the QAR technique was 83.36. The median in the pre-test was 76, but after learning with the QAR approach, it was 82. Prior to treatment, the experimental group's standard deviation was 1.676. After learning by applying QAR strategy, the standard deviation in the experimental group was 2.084. Students are more engaged in reading after employing the question-and-answer learning paradigm to improve their interest. This demonstrates that the question-and-answer interaction strategy's learning effect has a significant impact on students' success in reading narrative texts